Energy drinks: Pattern of consumption and associated factors among students in a Bangladeshi University. A cross-sectional study - Towhid Hasan; Marjia Sultana; Md. Tareq Hossain; Lima Khatun; Md. Alauddin (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - This research aimed to study patterns of energy drinks (ED) consumption among university students and to identify the determinants for their preferences. Design/methodology/approach - This cross-sectional study was conducted among 400 students from various departments of Jashore University of Science and Technology, Bangladesh, by convenience sampling. A self-administered, structured questionnaire was used to collect data. Findings - About 52.3 per cent of the students were between 21 and 23 years of age, and half of them were male. More than half (53 per cent) of the students had consumed ED at least once in their lifetime. Only 22.1 per cent of these consumers had any knowledge of the ingredients in ED, and 4.3 per cent did not know the possible negative impacts. Bivariate analysis was performed to identify the variables significantly associated with ED consumption among students. The risks of ED consumption were found to be: male gender (Odds Ratio (OR) = 4.04; 95 per cent Confidence Interval (CI) = 2.36-6.92), father educated up to SSC (OR = 18.47; 95 per cent CI = 2.30-148.90) or college and above (OR = 17.01; 95 per cent CI = 2.31-135.60), smoker (OR = 3.87; 95 per cent CI = 1.61-9.35) and doing irregular physical activity (OR = 2.43; 95 per cent CI = 1.23-4.78). Originality/value - ED consumption among university students is high, but their perception regarding the ingredients and potential health hazards is opaque. Therefore, it is imperative that at both community and individual levels, interventions should focus on educating and empowering individuals to make firm and positive decisions concerning their dietary habits and health.